SARS‐CoV‐2 Omicron BA.1 variant breakthrough infections in nursing home residents after an homologous third dose of the Comirnaty® COVID‐19 vaccine: Looking for correlates of protection. Issue 9 (25th May 2022) - Torres, Ignacio; Giménez, Estela; Albert, Eliseo; Zulaica, Joao; Álvarez‐Rodríguez, Beatriz; Burgos, Javier S.; Peiró, Salvador; Limón, Ramón; Vanaclocha, Hermelinda; Rodado, Celia; Botija, Pilar; Sifre, Amelia; et al.
Abstract: We investigated whether peripheral blood levels of SARS‐CoV‐2 Spike (S) receptor binding domain antibodies (anti‐RBD), neutralizing antibodies (NtAb) targeting Omicron S, and S‐reactive‐interferon (IFN)‐γ‐producing CD4 + and CD8 + T cells measured after a homologous booster dose (3D) with the Comirnaty® vaccine was associated with the likelihood of subsequent breakthrough infections due to the Omicron variant. An observational study including 146 nursing home residents (median age, 80 years; range, 66–99; 109 female) evaluated for an immunological response after 3D (at a median of 16 days). Anti‐RBD total antibodies were measured by chemiluminescent immunoassay. NtAb were quantified by an Omicron S pseudotyped virus neutralization assay. SARS‐CoV‐2‐S specific‐IFNγ‐producing CD4 + and CD8 + T cells were enumerated by whole‐blood flow cytometry for intracellular cytokine staining. In total, 33/146 participants contracted breakthrough Omicron infection (symptomatic in 30/33) within 4 months after 3D. Anti‐RBD antibody levels were comparable in infected and uninfected participants (21 123 vs. 24 723 BAU/ml; p = 0.34). Likewise, NtAb titers (reciprocal IC50 titer, 157 vs. 95; p = 0.32) and frequency of virus‐reactive CD4 + ( p = 0.82) and CD8 + ( p = 0.91) T cells were similar across participants in both groups. anti‐RBD antibody levels and NtAb titers estimated at around the time of infection were also comparable (3445 vs. 4345 BAU/ml; p = 0.59 and 188.5 vs. 88.9; p = 0.70, respectively). Having detectable NtAb against Omicron or SARS‐CoV‐2‐S‐reactive‐IFNγ‐producing CD4 + or CD8 + T cells after 3D was not correlated with increased protection from breakthrough infection (OR, 1.50; p = 0.54; OR, 0.0; p = 0.99 and OR 3.70; p = 0.23, respectively). None of the immune parameters evaluated herein, including NtAb titers against the Omicron variant, may reliably predict at the individual level the risk of contracting COVID‐19 due to the Omicron variant in nursing home residents.